Analisis Kemampuan Menggambar dengan Teknik Menggambar Angka Pada Siswa Kelas III SD N 02 Manggungmangu di Sekolah Dasar - Miftakhudin, Ahmad; Priyanto, Wawan; Cahyadi, Fajar (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
Drawing is one of the activities favored by elementary school students to develop creativity and the need for the right method in teaching it. The focus of this research is how the drawing ability of third grade students of State Elementary School 02 Manggungmangu is using the technique of drawing with numbers. This study aims to determine and analyze the drawing ability of third grade students of State Elementary School 02 Manggungmangu. This type of descriptive qualitative research with research subjects third grade students of State Elementary School 02 Manggungmangu. The data in the study were obtained through interviews, observation and documentation. The results showed that the third grade students of State Elementary School 02 Manggungmangu had good abilities after being given drawing treatment using number drawing techniques. It can be seen from the results of students' drawings using indicators of lancae aspects, detailed aspects, and original aspects. So this shows an increase in students' creative abilities in producing images using number drawing techniques.